Pengetahuan pengurusan berat badan di kalangan wanita bekerja di Kuala Lumpur - Poh B.K,; Sia P.H,; Norimah A. Karim,; Mohd Ismail Noor, (penerbit ukm, 2006)
Obesity prevalence and body image consciousness are on the rise, and women often try to lose weight using a variety of methods. This paper reports the knowledge on body weight management amongst working women aged 30 – 45 years in Kuala Lumpur. Respondents comprised 131 school teachers and 122 civil servants. Anthropometric measurements included body weight and height; while knowledge on weight management was assessed using a questionnaire. The respondents were Malay (64%), Chinese (26%) and Indian women (10%) with mean age of 38.3 ± 4.6 years old. The respondents were grouped into two weight categories based on body mass index (BMI): normal weight (BMI 18.5 to 24.9 kg/m2) and overweight (BMI ≥ 25.0 kg/m2). Mean body weight and BMI were significantly different (p < 0.001) between the two weight categories. Overweight and normal weight groups had mean body weight of 69.0 ± 9.5 kg and 53.5 ± 5.3 kg; while mean BMI were 29.2 ± 3.6 kg/ m2 dan 21.9 ± 1.7 kg/m2; respectively. Mean scores for knowledge on weight management were similar for both weight categories, 62.4 ± 13.7 and 61.8 ± 13.4 for overweight and normal weight, respectively. A majority of overweight (71%) and normal weight (73%) women had moderate level (scores 50–74%) of weight management knowledge. However, it was interesting to note that there were more overweight women (20%) who had high knowledge level(scores ≥ 75%) as compared to normal weight women (15%). Only 9% of overweight and 12% of normal weight women demonstrated low knowledge level (scores <50%). School teachers were significantly (p < 0.001) more knowledgeable than civil servants in weight management matters with mean knowledge scores of 65.5 ± 12.3 and 58.4 ± 13.9, respectively. On the whole, the results indicated that women were fairly knowledgeable in healthy body weight management. Knowledge on body weight management is essential for preventing comorbidity risks related to overweight problem. The study also revealed that there was a need for nutrition education related to body image and effective weight management.